Pengaruh Pertumbuhan Penjualan Terhadap Profitabilitas Perusahaan Dengan Kebijakan Hutang Sebagai Variabel Intervening - Riva Oktaviani; Ika Utami Widyaningsih (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this research is to analyze the effect of Sales Growth on Profitability mediated by Debt Policy (Case Study on Retail Trading Subsector Companies Listed on the Indonesia Stock Exchange for the 2012-2019 period. The research method used is a quantitative method. The sampling technique used is purposive sampling and the number of samples is 17 companies. The analytical method used is descriptive statistics, classical assumption test, regression analyst, hypothesis testing, path analysis and Sobel test which are tested through the SPSS program. The test results show that sales growth and debt policy have a significant positiveeffect on company profitability, beside that sales growth have a significant positive effect on a company's debt policy. In the mediation test, it is proven that debt policy is not able to mediate the effect of sales growth on the profitability of companies in the retail trade sub-sector.